Hubungan Tingkat Pengetahuan dan Sikap Keluarga Dengan TB Paru Pada Anak - Handayani, Welly; Citra M, Resi (Yayasan Jompa Research and Development, 2024)
According to the World Health Organization (Global TB Report, 2023) TB is still a health problem in the world today. TB is the second highest cause of death in the world after COVID-19 in 2022. Tuberculosis is a common cause of pain and death in children. The purpose of this research is to Know The Relationship between the Level of Knowledge and Family Attitudes with Pulmonary TB Disease in Children in the Working Area of the Air Santok Health Center, Pariaman City in 2024. This type of research is quantitative using the Cross Sectional Study design .The research was carried out at the Air Santok Health Center in 2024, carried out in October 2024. The sample in this study was 40 people from the suspected community of pulmonary TB in children. The results of this study found that 85% had high knowledge, 85% were kind, and 5% were positive for pulmonary TB in children. There was a relationship between knowledge level and Pulmonary TB in Children, with a p value of 0.019. There was a relationship between family attitudes and pulmonary TB in children, with a p value of 0.019. It is hoped that the Air Santok Health Center will provide counseling to the community, especially to families who have family members who experience pulmonary TB in children, providing about pulmonary TB disease should be further improved